Analysis of the Use of the Natural Exploration Method on Biodiversity Concepts on Senior High School Students’ Interest and Learning Motivation - Fitriana, Desi Eka Nur; Yunita, Erni; Hapidah, Lola Lolita Nur; Khotifah, Ummu Azizathul (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
This study aimed to evaluate the effect of the natural exploration method on senior high school students' interest and learning motivation on biodiversity concepts. This method is thought to provide a more interactive and enjoyable learning experience through student involvement with the surrounding environment. The study was conducted on grade X students at one of the senior high schools in Tangerang Regency, Indonesia with 145 grade X students as research subjects, using a qualitative descriptive approach in the form of Classroom Action Research (CAR). Data were collected through observation and Likert scale questionnaires. The results showed that the application of the natural exploration method increased students' interest and motivation. The highest percentage of interest in learning was found in the statement that the exploration method makes biodiversity learning more interesting (53.8%), while the highest learning motivation was seen in students who felt more enthusiastic about learning biodiversity after the exploration activity (53.8%). However, some students admitted that they had difficulty understanding the teacher's explanation (33.8%) and rarely looked for additional information (40.1%). In conclusion, the natural exploration method is effective in increasing students' interest and motivation in learning, although improvements are still needed in several aspects of learning.